A Clinical PET Imaging Tracer ([18F]DASA-23) to Monitor Pyruvate Kinase M2–Induced Glycolytic Reprogramming in Glioblastoma - Beinat, Corinne; Patel, Chirag B.; Haywood, Tom; Murty, Surya; Naya, Lewis; Castillo, Jessa B.; Reyes, Samantha T.; Phillips, Megan; Buccino, Pablo; Shen, Bin; Park, Jun Hyung; Koran, Mary Ellen I.; et al. (Clinical cancer research, 2021)
Pyruvate kinase M2 (PKM2) catalyzes the final step in glycolysis, a key process of cancer metabolism. PKM2 is preferentially expressed by glioblastoma (GBM) cells with minimal expression in healthy brain. We describe the development, validation, and translation of a novel PET tracer to study PKM2 in GBM. We evaluated 1-((2-fluoro-6-[ F]fluorophenyl)sulfonyl)-4-((4-methoxyphenyl)sulfonyl)piperazine ([ F]DASA-23) in cell culture, mouse models of GBM, healthy human volunteers, and patients with GBM. [ F]DASA-23 was synthesized with a molar activity of 100.47 ± 29.58 GBq/μmol and radiochemical purity >95%. We performed initial testing of [ F]DASA-23 in GBM cell culture and human GBM xenografts implanted orthotopically into mice. Next, we produced [ F]DASA-23 under FDA oversight, and evaluated it in healthy volunteers and a pilot cohort of patients with glioma. In mouse imaging studies, [ F]DASA-23 clearly delineated the U87 GBM from surrounding healthy brain tissue and had a tumor-to-brain ratio of 3.6 ± 0.5. In human volunteers, [ F]DASA-23 crossed the intact blood-brain barrier and was rapidly cleared. In patients with GBM, [ F]DASA-23 successfully outlined tumors visible on contrast-enhanced MRI. The uptake of [ F]DASA-23 was markedly elevated in GBMs compared with normal brain, and it identified a metabolic nonresponder within 1 week of treatment initiation. We developed and translated [ F]DASA-23 as a new tracer that demonstrated the visualization of aberrantly expressed PKM2 for the first time in human subjects. These results warrant further clinical evaluation of [ F]DASA-23 to assess its utility for imaging therapy-induced normalization of aberrant cancer metabolism.